Kegiatan sosialisasi kesehatan dan vaksinasi ternak sapi potong di Desa Tihengo, Kabupaten Gorontalo Utara - Agus Bahar Rachman; Haris Umar; Hesti Amri Ulan (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
Archipelago and coastal communities need to improve their economic level apart from the fishery sector as well as from the livestock sector. Tihengo Village is an archipelago and coastal area part of the Ponelo Islands District, North Gorontalo Regency. Therefore, it is necessary to support the implementation of livestock health management in order to increase livestock productivity. This service aims to obtain information about livestock health, livestock management, and disease prevention patterns in livestock so that it can improve the economy of beef cattle farmers. Service activities in the form of “Kuliah Kerja Nyata” (KKN) – Thematic activities are carried out in the form of health services by collecting cattle in a place in the form of giving vitamins, deworming medicine and spraying on healthy livestock, and treating sick cattle, as well as discussions with farmers. about the importance of maintaining the health of livestock. The target of the service activity is in the form of discussions with cattle breeders and health services for Bali cattle from 3 Sub Village in Tihengo Village. The number of cattle served in this implementation was 22 cattles. Health services for livestock include the provision of vitamins (22 cattles), deworming medicine (21 cattles), spraying butox (22 cattles), and ivomec injection (4 cattles) for animals experiencing itching on the skin injection (4 Cows) for animals experiencing itching on the skin.